River to redemption [large type] - Gabhart, Ann H., 1947- (Center Point Large Print, 2018)
"Orphaned in the cholera epidemic of 1833, Adria Starr was cared for by a slave named Louis in Springfield, Kentucky. Twelve years later, nineteen-year-old Adria is determined to find a way to buy Louis's freedom. But in 1840s Kentucky, she'll face an uphill battle. Based partly on a true story"--